Insights into Holocene relative sea-level changes in the southern North Sea using an improved microfauna-based transfer function - Scheder, Juliane; Bungenstock, Friederike; Haynert, Kristin; Pint, Anna; Schlütz, Frank; Frenzel, Peter; Wehrmann, Achim; Brückner, Helmut; Engel, Max (Journal of quaternary science, 2022)
In light of global warming and rising relative sea level (RSL), detailed reconstructions of RSL histories and their controlling processes are essential in order to manage coastal-protection challenges. This study contributes to unravelling Holocene RSL change on the East Frisian North Sea coast in high resolution and with a new approach for the German Bight. For the first time, a transfer function (vertical error: 29.7 cm ≙ 11% of the mean tidal range) for RSL change based on a combined training set of benthic foraminifers and ostracods from the back-barrier tidal basin of Spiekeroog is applied to the Holocene record of the back-barrier tidal basin of Norderney. The resulting RSL curve for the Norderney tidal basin is corrected for decompaction and shows a deceleration in RSL rise between 6000 and 5000 cal bp. The smallest possible error envelope ( 1 m) results from the good suitability of salt-marsh layers between 5000 and 4000 cal bp. The RSL curve provides an approach towards the closure of the common data gap of peat-based curves for the southern North Sea related to a lack of basal peats in the youngest age range, and verifies regional differences in glacial isostatic adjustment.
Online veröffentlicht: 11. Oktober 2021
Gesehen am 29.10.2025